Janet Bately 1993: Anonymous Old English Homilies. A Preliminary Bibliography of Source Studies. Binghamton, Center for Medieval and Early Renaissance Studies, State University of New York (SUNY) - Campos, Xavier (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen